Pemanfaatan Teknologi Informasi dan Komunikasi di bidang Kesehatan di Masyarakat - Alfan Najmi; Ricky Wiranata; Astri Khoir K (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2026)
The development of Information and Communication Technology (ICT) in the healthcare sector has provided various conveniences in accessing digital health services, such as online consultations, medication ordering, and access to health information through Android-based applications. However, the utilization of these technologies in the community remains suboptimal due to low levels of digital literacy and limited public trust in health applications. This community service activity aimed to improve public knowledge, skills, interest, and trust in using Android-based health applications. The activity was conducted through counseling sessions and hands-on workshops for residents of Alfatih Regency Phase IV, Tenayan Raya, Pekanbaru City. The results showed improvements across all indicators after the implementation of the program. Public knowledge, capabilities, and trust in health applications are increasing. The N-Gain analysis demonstrated high-category improvements in knowledge (0.79) and application usage skills (0.73), while interest (0.58) and trust (0.54) were categorized as moderate. This activity proved effective in improving community digital literacy in the healthcare sector and can serve as an initial step toward broader utilization of digital health services within the community.